2022
DOI: 10.48550/arxiv.2203.14234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Making a case for femto- phono- magnetism with FePt

Abstract: In the field of femtomagnetism magnetic matter is controlled by ultrafast laser pulses; here we show that coupling phonon excitations of the nuclei to spin and charge leads to femto-phono-magnetism, a powerful route to control magnetic order at ultrafast times. With state-of-the-art theoretical simulations of coupled spin-charge-and lattice-dynamics we identify strong non-adiabatic spinphonon coupled modes that dominate early time spin dynamics. Activating these phonon modes we show leads to an additional (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…A recent study based on a combination of TDDFT and dynamical mean-field theory [18] demonstrated that the usually missing memory effects in exchange-correlation functionals play a key role in the proper description of the amount of demagnetization induced by light, and that including them leads to a larger demagnetization. The role of phonons is also starting to be investigated [19]. These studies partly fill the gap between theoretical predictions and experiments but the picture is far from complete.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study based on a combination of TDDFT and dynamical mean-field theory [18] demonstrated that the usually missing memory effects in exchange-correlation functionals play a key role in the proper description of the amount of demagnetization induced by light, and that including them leads to a larger demagnetization. The role of phonons is also starting to be investigated [19]. These studies partly fill the gap between theoretical predictions and experiments but the picture is far from complete.…”
Section: Introductionmentioning
confidence: 99%